Factors that facilitate and hinder the return to work after stroke: an overview of systematic reviews - La Torre, Giuseppe; Lia, Lorenza; Francavilla, Federico; Chiappetta, Marta; De Sio, Simone (La Medicina del Lavoro, 2022)
Background: Stroke is one of the leading causes of death and disability in the industrialized world and a large part of stroke survivors is of working age. A very important goal for these people is to return to work after stroke as it facilitates independent living and guarantees a high level of self-esteem and life satisfaction. Aim: To find the main factors that facilitate and hinder the return to work (RTW) in people who suffered from stroke through an overview of systematic reviews. Methods: A systematic search using keywords and medical subject heading terms was conducted in January 2022, three electronic databases were searched: Medline (PubMed), Scopus and ISI Web. The articles that address the question of returning to work or maintaining employment of people of working age after stroke were included in the systematic review, as well as studies describing factors that facilitate and/or hinder RTW after stroke. Only systematic reviews written in English language were included in this overview. Results: The search revealed 180 records after removing duplicates, but only a total of 24 systematic reviews were included in the overview. This research shows that in people who have suffered from a stroke, individual abilities, socioeconomic factors, healthcare factors, and disabilities resulting from the stroke itself are the most critical factors influencing the RTW. Conclusion: Future research should focus on cognitive disabilities, as main RTW hindering factor, and vocational rehabilitation, as the more suitable factor for improving the RTW in stroke survivors.